2019
DOI: 10.1111/tbj.13435
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and beliefs toward the use of stereotactic body radiotherapy in oligometastatic breast cancer: A commentary on a survey of Canadian Medical Oncologists

Abstract: Stereotactic body radiotherapy (SBRT) is a highly ablative local therapy which has emerged as part of the treatment paradigm for patients with oligometastatic (OM) breast cancer (defined by 5 or fewer sites). This patient group has demonstrated improved prognosis in some cases and may therefore, benefit from aggressive local treatment. The role of upfront SBRT in newly diagnosed OM breast cancer in addition to systemic therapy is not clear, yet it is being increasingly utilized within the oncology community. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…The above mentioned survey of Canadian medical oncologists revealed a high proportion of doubt considering SBRT for oligometastastic breast cancer (18). Studies investigating high dose chemotherapy for metastatic breast cancer were mainly conducted when Weichselbaum and Hellman developed their theory of OMD in the 1990s (1,46).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The above mentioned survey of Canadian medical oncologists revealed a high proportion of doubt considering SBRT for oligometastastic breast cancer (18). Studies investigating high dose chemotherapy for metastatic breast cancer were mainly conducted when Weichselbaum and Hellman developed their theory of OMD in the 1990s (1,46).…”
Section: Discussionmentioning
confidence: 99%
“…This is a surprising fact, considering a 10 year OS of up to 75% in breast cancer patients with single bone metastases which surmounts the OS of many other tumors, even in their early stage ( 4 ). A survey of Canadian medical oncologists revealed that 65% would rather start systemic therapy in breast cancer patients with OMD, than even consider a SBRT at all ( 18 ). As SBRT for oligometastatic breast cancer patients is a relatively new disease concept, most studies in this area only include a small number of patients and mostly consist of only one specific ( 5 ) or predominant ( 19 21 ) location of metastases.…”
Section: Background and Purposementioning
confidence: 99%
“…Due to the limited extent of disease burden, OMBC lends itself nicely to non-invasive modalities with high precision, such as radiotherapy, and indeed this has been utilized with increasing frequency [21]. Until recently, most data supporting its use came from retrospective and prospective non-randomized, mostly single arm studies (see Table 1 for list of selected studies) [22,23,[32][33][34][35][36][24][25][26][27][28][29][30][31].…”
Section: Radiation Therapy In Ombcmentioning
confidence: 99%
“…As systemic therapies improve, it raises the question as to whether they negate the benefit of targeted radiotherapy, although there is also the possible synergy between radiation and immunotherapy generating an abscopal response [ 32 ]. Next, in a study of medical oncologists, 86.7% of respondents felt that SBRT could delay growth of metastases and prevent symptoms, and 73% would refer for both symptomatic and asymptomatic metastases [ 33 ]. However, the belief did not apply to all patients, as only 63.3% and 50% of respondents were comfortable referring patients with HER2-positive and triple-negative subtypes, respectively.…”
Section: Discussionmentioning
confidence: 99%